Motivacija za izobraževanje in usposabljanje generacije Y in Z v lesarstvu - Goropečnik, Luka (Les (Ljubljana), 2021)
With Industry 4.0, we are entering the digital age, which will significantly change the profiles of employees and their necessary competencies. This also affects education in the field of wood related sector. The aim of the research was to find out which teaching methods in learning motivate representatives of generations Y and Z at different levels of education (from vocational to master degree education) in wood related sector, which way of education is most suitable and what they think about distance learning. To this end, we conducted a survey using social media and e-classroom. The results showed that learners are most motivated by an environment that strives for development, is safe and stable, and by teamwork, while they do not desire a competitive environment. We did not find much difference in motivational factors between groups at different levels of education and ways of education (full-time, lifelong). Otherwise, the main motivation of learners in woodworking, regardless of generation, is the internal incentives of the individual, while the external incentives differ more between generations
Keywords: digital age; digitalna doba; education; generacija Y; generacija Z; generation Y; generation Z; izobraževanje; lesarstvo; motivacija; motivation; wood sector